Correlación de la inteligencia emocional y el aprendizaje significativo de los alumnos y alumnas del cuarto año de educación secundaria de la I.E. Virgen Dolorosa del distrito de la Banda de Shilcayo San Martín - Callo Paye, Ana Patricia (2006)
Descriptive method utilized correlacional once was accomplished with pupils and the fourth secondary- education year's schoolgirls in the educational institution itself In the present fact-finding work Virgen Dolorosa, in Shilcayo's Banda's district, San Martín's province during the year 2005. This study permitted establishing the relation of the Inteligencia Emocional and the Aprendizaje Significativo, in the education quality in the Social sciences area to us. lnvestigation was structured considering the variables's correlation: Emotional lntelligence and existent Aprendizaje Significativo among them. lt was worked up with 100 pupils's aleatory sign, he elaborated previously a test to measure Inteligencia Emocional's grade, based in five fields: The autoconscience, the self-control, the motivation, the empathy and the social connections. lt was evaluated in 4 two-month periods all year round academic to measure the Aprendizaje Significativo, obteniéndose the final note that went once was provided of the official minutes. Next one proceeded to recollect the information in order to his respective analysis of correlation of Pearson giving us a positive correlation weak ofi =0,169; In the pupils and the fourth year's schoolgirls of her secondary education l.E. Painful Virgin of the district of Shilcayo's Banda, San Martín, year 2005. In conclusion it is determined than the Inteligencia Emocional play a very important role in the Aprendizaje Significativo's achievement, he relates with the need of inducing interest to the pupil and necessary labors, he is the professor's work to offer direction and guide pertinent in each situation motivation only is not in charge of the teacher, destiny also the parents are implicated and the society; That reflection process will be a first step on the way over toward the teaching's invention that will be fruitful. The professors must apply strategies in order to a best learning in the pupil; Because education is one of the halfway main things available to promote a human development plus prorustic farm and harmonious, to do to move back the poverty, the exclusion, the ignorance, the oppression, the war, etc.